Pesantren-Based Islamic Education: Learning Strategies for Memorizing the Qur’an in Islamic Boarding Schools (Pesantren) - Saepudin Saepudin; Suhirman Suhirman; Nurlaili Nurlaili; Alfauzan Amin (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Pesantren-Based Islamic Education: Learning Strategies for Memorizing the Qur’an in Islamic Boarding Schools (Pesantren)Objective: This study analyzes the learning strategies used by students (santri) for memorizing the Qur’an at Pesantren As-Salam. Methods: This research is a field study employing a qualitative approach, involving direct observation, in-depth interviews with santri, ustaz, and pesantren administrators, as well as analysis of relevant documents. Results: Santri at Pesantren As-Salam employ various memorization techniques, including talaqqi, tikrar, wahdah, muraja'ah, and sima'an, often combining these methods to enhance memorization effectiveness. Key supporting factors include the disciplined environment of the pesantren, intensive guidance from teachers, a rigorous evaluation system, and strong intrinsic motivation among the students. Conclusion: The implementation of a structured tahfidz strategy, alongside the integration of digital technology, can significantly improve the effectiveness of Qur’an memorization. Contribution: This study offers insights into effective tahfidz strategies within the pesantren system and provides recommendations for integrating technology and adapting memorization methods to the characteristics of santri, to enhance future memorization outcomes.INDONESIAN: Pendidikan Islam Berbasis Pesantren: Strategi Pembelajaran Menghafal Al-Qur'an Santri di PesantrenTujuan: Penelitian ini bertujuan untuk menganalisis strategi pembelajaran yang diterapkan oleh santri dalam menghafal Al-Qur'an di Pesantren As-Salam. Metode: Jenis penelitian menggunakan studi lapangan dengan pendekatan kualitatif, yang melibatkan observasi langsung, wawancara mendalam dengan santri, ustaz, serta pengelola pesantren, dan analisis dokumen terkait. Hasil: Santri di As-Salam menggunakan berbagai metode hafalan, antara lain talaqqi, tikrar, wahdah, muraja’ah, dan sima’an, yang dikombinasikan untuk meningkatkan efektivitas hafalan. Faktor pendukung utama dalam keberhasilan hafalan adalah lingkungan pesantren yang disiplin, bimbingan intensif dari pengajar, sistem evaluasi yang ketat, serta motivasi intrinsik dari santri itu sendiri. Kesimpulan: Penerapan strategi tahfidz yang terstruktur dan penggunaan teknologi digital dapat meningkatkan efektivitas menghafal Al-Qur’an. Kontribusi: Penelitian memberikan wawasan tentang strategi tahfidz yang efektif di pesantren, serta rekomendasi untuk mengintegrasikan teknologi dan menyesuaikan metode dengan karakteristik santri untuk meningkatkan keberhasilan hafalan Al-Qur’an di masa depan.